Working Capital Management And Its Impact On Firms Performance: An Analysis Of Listed Manufacturing Companies In Sri Lanka. - Ananthasayanan, S.; Subramaniam, V.A. (University of Jaffna, 2010)
A well designed and implemented working capital management is expected to contribute positively to the creation of a firm’s value. The purpose of the paper is the relationship between working capital management and its impact on firm’s performance. In this study, 25 manufacturing companies out of 31 are selected as sample. The depended variable, net profit ratio is used as a measure of firm’s performance and the relationship between working capital management and performance is investigated using panel data analysis for the period 2003 2007, the regression results show that high investment in inventories and receivable is associated with lower profitability. The key variables used in the analysis are inventory conversion cycle. A strong significant relationship between working capital management and profitability has been found in previous empirical work. The findings also reveal working capital management impact on profitability of manufacturing industries.
Keywords: Working capital ,management; Inventory conversion periods; Creditors conversion; Net profit ratio; Cash conversion cycle